The Impact of the Human Rights Convention on the Development of the Administrative Judiciary of Ukraine - Стрельников, Андрій Вікторович; Стрельников, А. В.; Стрельников, Андрей Викторович; Strelnykov, Andrii V.; Strelnykov, Andriy; Сандул, Яна Миколаївна; Сандул, Я. М.; Сандул, Яна Николаевна; Sandul, Yana M. (VD "Dakor", 2021)
The administration of justice on the basis of a fair trial is not an easy task, as both parties to the dispute are usually certain of their rightness, which they are trying to prove to the court. If one of these parties is a state or its bodies, the judiciary can become a dangerous tool to influence any process in society. Specific cases against The administration of justice on the basis of a fair trial is not an easy task, as Ukraine show that high-ranking officials of all periods of power did not neglect the possibility of influencing the outcome of the case, pursuing goals not related to the administration of justice. The influence of the European Convention and the case law of the European Court of Human Rights has become decisive for Ukraine in the formation of a separate procedure for the administration of justice: administrative proceedings. Some aspects of its functioning are investigated in this work, in particular, the preconditions for the differentiation of administrative proceedings in Ukraine, the problem of defining the concept of the authorities and the state as a party to the case, the implementation of the right to a fair trial in administrative proceedings, access to court and the principle of the equality of parties; oral and open administrative proceedings; adversarial proceedings and the right of the court to establish the circumstances of the administrative case.

Здійснення правосуддя на основі справедливого судового розгляду є непростим завданням, оскільки обидві сторони спору, як правило, впевнені у своїй правоті, що й намагаються довести суду. Якщо однією з цих сторін є держава або її органи, судова влада може стати небезпечним інструментом впливу на будь-який процес у суспільстві. Конкретні справи проти здійснення правосуддя на засадах справедливого судового розгляду є непростим завданням, оскільки Україна показує, що високопосадовці всіх періодів влади не нехтували можливістю вплинути на результат справи, переслідуючи цілі, не пов’язані із здійсненням правосуддя. Вплив Європейської конвенції та практики Європейського суду з прав людини став визначальним для України у формуванні окремої процедури здійснення правосуддя: адміністративного судочинства. У цій роботі досліджуються окремі аспекти його функціонування, зокрема, передумови диференціації адміністративного судочинства в Україні, проблема визначення поняття органів влади та держави як сторони у справі, реалізації права на адміністративне судочинство, справедливий суд в адміністративному судочинстві, доступ до суду та принцип рівності сторін; усні та відкриті адміністративні провадження; змагальність провадження та право суду на встановлення обставин адміністративної справи.
Sandul Ya. The Impact of the Human Rights Convention on the Development of the Administrative Judiciary of Ukraine / Ya. Sandul, A. Strelnykov // AJEE Journal. - № 1(9). - VD "Dakor", 2021. - Р. 223-231.
Keywords: administrative proceedings; the right to a fair trial; access to court; the principle of equality of parties; oral and open administrative proceedings; the right of the court to establish the circumstances of the administrative case; адміністративне судочинство; право на справедливий суд; доступ до суду; принцип рівності сторін; усні та відкриті адміністративні провадження; право суду встановити обставини адміністративної справи; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Administrative procedure